The Effect of Company Size, Profitability, Audit Opinion And Company Age on Audit Delay on Property and Real Estate Companies in BEI - Pyes Mitra Laia; Risma Br. Purba; Tetty Tiurma Uli Sipahutar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to determine the effect of company size, profitability, audit opinion, and company age on audit delay in property and real estate companies listed on the Indonesia Stock Exchange in 2018-2020. This study uses secondary data that can be accessed through the Indonesia Stock Exchange website (www.idx.co.id) in the form of company financial statements. The data analysis technique used was descriptive statistical analysis, t test, F test, and multiple regression analysis using SPSS software (Statistical Package for the Social Science) version 25. The population of this study consisted of 65 companies in the Property & Real Estate sector and methods Sampling was done by purposive sampling method. With this method, a sample of 44 companies was obtained with an observation period of 3 years (2018-2020), so the number of samples for this study was 132 observations. Based on the results of the study, partially company size, profitability, audit opinion and company age have a negative effect on audit delay. The results of the study simultaneously show that the variables of firm size, profitability, audit opinion and firm age have no simultaneous effect on audit delay.